Chorea. Issue 5 (October 2022) - Stimming, Erin Furr; Bega, Danny
ABSTRACT: PURPOSE OF REVIEW: This article provides an overview of the diagnostic and therapeutic approach to a patient with chorea. The phenomenology of chorea is described in addition to other common hyperkinetic movements that may be mistaken for or coexist with chorea. Chorea can be acquired or hereditary. Key historical and clinical features that can aid in determining the etiology are reviewed, and pharmacologic and nonpharmacologic treatment strategies are discussed. RECENT FINDINGS: Clinical investigations are under way to target transcription and translation of the mutant huntingtin protein as a potential disease-modifying strategy in Huntington disease (HD). Additional heritable factors have been revealed through genome-wide association studies. Symptom-focused treatments for HD are are being studied, including a third vesicular monoamine transporter-2 (VMAT2) inhibitor for chorea attenuation and drugs to target irritability and cognitive impairment. Increased availability of genetic testing has led to increased awareness of HD mimics (eg, C9orf72 and IgLON5). SUMMARY: Chorea is a relatively common hyperkinetic disorder with a broad differential. The first step in the approach to a patient with chorea is accurately defining the phenomenology. Once it has been determined that the patient has chorea, the investigation into determining an etiology can begin. Factors such as age of onset, time course, family history, unique clinical features, and imaging and laboratory findings can guide the diagnosis. Treatments for most causes of chorea are purely symptomatic, although it is important to recognize causes that are reversible or have disease-modifying interventions.